The investigation of the transport system for fright owners servicing in the traffic centres - Nahornyi, Ye. V.; Okrokov, A. M.; Peresta, H. I. (Science and Transport Progress, 2011)
The development of research activities related to operation of transport junctions and improvement of transport services at them for freight owners, co-operation of separate modes of transport in a junction and upgrading the quality of transportations is examined.